Body composition and basal metabolic rate in Hidradenitis Suppurativa: a Danish population‐based and hospital‐based cross‐sectional study. (9th December 2015) - Miller, I.M.; Rytgaard, H.; Mogensen, U.B.; Miller, E.; Ring, H.C.; Ellervik, C.; Jemec, G.B.
Abstract: Background: Several studies have suggested an association between Hidradenitis Suppurativa (HS) and obesity. Obesity is often expressed as Body Mass Index (BMI). However, BMI lacks information on body composition. General obesity is a predictor of health status and cardiovascular risk, but body composition (e.g. abdominal fat) may be more so. Basal metabolic rate (BMR) is an expression of resting metabolism and may serve as a complementary tool when assessing the possibly underlying metabolism behind a persons' body composition. Objective: To investigate the body composition and basal metabolic rate in individuals with HS compared with healthy controls. Methods: We performed a cross‐sectional study on both a hospital‐based and population‐based HS group and compared with controls using Bioelectrical Impedance Analysis to assess body composition. Results: We identified a hospital‐based HS group of 32 hospital HS patients, a population‐based HS group of 430 population HS patients, and 20 780 controls. Age‐ and sex‐adjusted analyses showed a 10.12% ( P < 0.0001) significantly higher fat percentage in the hospital‐based HS group and 3.11% ( P < 0.0001) significantly higher fat percentage for the population‐based HS group compared to controls. Correspondingly, the HS groups had a lower muscle percentage ( P < 0.0001) and lower bone mass percentage ( P < 0.0001). Furthermore, visceral fat rating ( P < 0.0001), Body Mass Index ( P < 0.0001), waist circumference ( P < 0.0001), and Waist/Hip Ratio ( P < 0.0001) was significantly higher in HS patients compared with controls. Additionally, age and sex‐adjusted analyses showed a higher predicted estimate of BMR for the HS groups compared with controls (154.56 kcal/day (95% CI 54.96–254.16) ( P = 0.0031) for the hospital‐based HS group, and 82.63 kcal/day (95%CI 59.70–105.56) ( P < 0.0001) for the population‐based HS group). Conclusion: Hidradenitis Suppurativa is associated with a high fat percentage, high visceral fat, and low muscle percentage adding to the morbidity of HS. The higher predicted estimate of basal metabolic rate (BMR) in HS patients may reflect a dysfunctional metabolism contributing to the high‐fat‐body composition.